PEMANFAATAN LIMBAH SAGU SEBAGAI BAHAN PAPAN PARTIKEL - Suwandi Kliwon; Rozak Memed (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The experiment result of using sago waste for particleboard is reported in this paper. The experiment covers the process of making particleboard with several raw material compositions and testing their physical and mechanical properties. The particleboard is bonded with urea formaldehyde resin with the dimension of 30 cm x 30 cm x 1,5 cm,The results indicate that most of the physical properties of particleboard meet Indonesian or FAO standards, while many of mechanical properties do not meet those standards. Veneer lamination improves the bending strength and the addition of sago bark do not improve physical and mechanical properties of particleboard.